2014
DOI: 10.1016/j.ijsbe.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of benchmarking approaches for non-domestic buildings: Part 2 – Bottom-up approach

Abstract: The bottom-up methods for energy benchmarking aim to derive a yardstick for energy performance based on a theoretical analysis of a building. While the top-down methods drive performance improvement by ranking a building against its peers, the bottom-up methods are focused on the building's specific context. Consequently, the bottom-up methods can help identify how performance improvement could be materialised. These two complementary approaches can improve design practice and facilities' management. Two botto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Several sources have addressed the classification of building performance evaluation methodologies. A recent two-part study separates top-down (deductive) benchmarking methodologies involving statistical approaches [21] from bottom-up (inductive) methodologies which use aggregated end-use calculations or building simulation [22]. Other studies have categorised benchmarking through black, grey or white box methodologies [23], where these are defined as follows:…”
Section: Classification Of Performance Evaluation Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several sources have addressed the classification of building performance evaluation methodologies. A recent two-part study separates top-down (deductive) benchmarking methodologies involving statistical approaches [21] from bottom-up (inductive) methodologies which use aggregated end-use calculations or building simulation [22]. Other studies have categorised benchmarking through black, grey or white box methodologies [23], where these are defined as follows:…”
Section: Classification Of Performance Evaluation Methodologiesmentioning
confidence: 99%
“…White-box Black box (sometimes grey box) [23], [26], [27] Bottom-up Top-down [21], [22] Forward modelling Data-driven modelling or inverse modelling [24], [28], [29] Benchmarking [15] Simple calculation The selection of the most appropriate analysis method will generally depend on the following factors: accuracy, sensitivity, versatility, speed, cost, reproducibility and ease of use [24].…”
Section: Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies established benchmarking models for diagnosing a building's dynamic energy performance using various approaches, such as the engineering, statistical, and hybrid approaches (refer to Table 7) [70,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123].…”
Section: Benchmarking a Building's Dynamic Energy Performancementioning
confidence: 99%
“…This can be done in two different ways: (i) by calculating the theoretical energy performance of a building using equations; and (ii) by calculating the theoretical energy performance of a building with simulation tools. Burman et al [107] used the building physics method (i.e., UK National Calculation Methodology (NCM)) and aggregated end-use (i.e., the Technical Memorandum 22 (TM22) methodology) to develop a benchmarking model for diagnosing the dynamic energy performance of school buildings in the UK. The results showed that the energy benchmarks derived from the proposed method could be used as the baselines for diagnosing a building's dynamic energy performance, but it might not be practical for all buildings due to its complexity.…”
Section: Benchmarking a Building's Dynamic Energy Performancementioning
confidence: 99%